Physicochemical Properties and Shelf-Life Evaluation of Nutrient Fortified Dehydrated Tofu for Satiety - Fathul Rahman, Fathul Naeem; Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2024)
Nutrient fortified dehydrated tofu are dehydrated fried tofu puffs that have vitamin supplements added into it in order to give a feeling of sustenance as well as provide nutrients. Satiating and nutritious foods come in useful in scenarios where hunger needs to be alleviated temporarily through the consumption of a compact and nutrient dense food . The physicochemical properties and shelf-life of NFDT was investigated along with assessing the satiation effect associated with its working principle. The physicochemical properties that were investigated were water-holding capacity where NFDT had higher WHC at 92.85 ± 1.14 %, colour analysis, and texture, where there was significant difference between the two dehydrated samples and two undehydrated samples. Meanwhile, NFDT gave moisture content of 5.38 ± 0.19. NFDT and CDT also had similar energy values. The fortification of tofu with vitamin supplement tablets also proved success because NFDT exhibited a vitamin B12 content of 400.29 mg per 100 g while CDT exhibited none. This proves that the tofu is fortified with vitamins. NFDT also was shown to be dehydrated sufficiently.